CENP‐R acts bilaterally as a tumor suppressor and as an oncogene in the two‐stage skin carcinogenesis model. Issue 11 (30th August 2017) - Okumura, Kazuhiro; Kagawa, Naoko; Saito, Megumi; Yoshizawa, Yasuhiro; Munakata, Haruka; Isogai, Eriko; Fukagawa, Tatsuo; Wakabayashi, Yuichi
Abstract : CENP‐R is a component of the CENP‐O complex, including CENP‐O, CENP‐P, CENP‐Q, CENP‐R, and CENP‐U and is constitutively localized to kinetochores throughout the cell cycle in vertebrates. CENP‐R‐deficient chicken DT40 cells are viable and show a very minor effect on mitosis. To investigate the functional roles of CENP‐R in vivo, we generated CENP‐R‐deficient mice ( Cenp ‐ r −/− ). Mice heterozygous or homozygous for Cenp‐r null mutation are viable and healthy, with no apparent defect in growth and morphology, indicating Cenp‐r is not essential for normal development. Accordingly, to investigate the role of the Cenp‐r gene in skin carcinogenesis, we subjected Cenp ‐ r −/− mice to the 7, 12‐dimethylbenz(a)anthracene (DMBA)/TPA chemical carcinogenesis protocol and monitored tumor development. As a result, Cenp ‐ r −/− mice initially developed significantly more papillomas than control wild‐type mice. However, papillomas in Cenp ‐ r −/− mice showed a decrease of proliferative cells and an increase of apoptotic cells. As a result, they did not grow bigger and some papillomas showed substantial regression. Furthermore, papillomas in Cenp ‐ r −/− mice showed lower frequency of malignant conversion to squamous cell carcinomas. These results indicate Cenp‐r functions bilaterally in cancer development: during early developmental stages, Cenp‐r functions as a tumor suppressor, but during the expansion and progression of papillomas it functions as a tumor‐promoting factor. Abstract : Cenp‐r functions bilaterally in cancer development: during early developmental stages, Cenp‐r behaves as a tumor suppressor, but during the expansion and progression of papillomas it behaves as a tumor‐promoting factor.